COVID-19 And Nepal: A Gender Perspective - Nepal, Samata; Aryal, Shreyashi (Journal of Lumbini Medical College, 2020)
The ongoing Corona Virus Disease 19 (COVID-19) pandemic is in its height, the measures taken to control the spread of this pandemic is acute and harsh. With the increasing new cases every hour it has caused a panic among every individual. Economy of the countries are equally affected. However, the direct and indirect impact of this pandemic on gender related needs are least prioritized and discussed. Evidences so far reveal the mortality being proportionately higher in males.This fact may not remain the same in Nepalese context because women are more vulnerable in this low-income country where limited resources are allotted to women’s health. Majority of the workforce at frontline health care are women in the form of nurses, midwives and female community health volunteers (FCHV). Government of Nepal has decided to mobilize FCHVs for COVID-19 response in the community and these FCHVs who provide services at ground levels are at occupational risk of acquiring the infection.